Formulasi Tablet Ibuprofen Dengan Eksipien Pati Beras (Oryza Sativa L.) Pregelatinasi Dan Polyvinyl Pyrrolidon Menggunakan Metode Simplex Lattice Design - Wibowo , Farrel Maulana; Rahmawati, Juwita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Rice starch is a natural material that can be used as a tablet disintegrant to reduce reliance on synthetic pharmaceutical excipients, but it has poor flowability and low bulk density. Pregelatinization is one way to improve the physical properties of starch as a tablet disintegrant. This study aims to optimize the ibuprofen tablet formula using a combination of pregelatinized rice starch as a disintegrant and polyvinyl pyrrolidone as a binder. Both materials are optimized using the Design Expert V13 program using the Simplex Lattice Design method. The parameters of the granules evaluated include flow rate, angle of repose, and compressibility index. For tablets, physical properties are tested including hardness, brittleness, and disintegration time, as well as weight diversity for the optimal formula. Furthermore, verification is carried out for the optimal formula and weight diversity tests are added. The optimal ibuprofen tablet formula obtained is for 5.5% pregelatinized rice starch and 5% PVP with a desirability value of 0.909 shows the optimal design because the desirability value range is in the range 0-1. Confirmation of the optimal formula based on its physical properties includes a flow rate test of 11.96 g/s ± 0.06, an angle of repose of 32.06º ± 0.75, a compressibility index of 14.84% ± 2.65, a tablet hardness of 7.29 kg ± 0.28, a tablet friability of 0.63% ± 0.19, a tablet disintegration time of 11.02 minutes ± 0.07, and a weight diversity of 96.96% and NP of 8.324. The results of physical tests show that the optimal formula meets the requirements for good physical properties of tablets